Cyathus tongxinianus sp. nov. (Basidiomycota) from China - Duan, Zi-Yan; Yang, Xin; Li, Qi; Yao, Lu; Zhao, Chang-Lin (Phytotaxa, 2023)
A new species of bird’s nest fungus, Cyathus tongxinianus, is proposed based on a combination of morphological and molecular evidence. Cyathus tongxinianus is characterized by the cupulate to obconical basidiomata with the smooth outer and inner surface of the peridium, a dimitic hyphal system of peridium walls with generative hyphae having clamp connections, the presence of the fimbriate mouth, brown black to dark grey peridioles, a monomitic hyphal system bearing the generative hyphae with clamp connections, the presence of crystals, and sub-globose, thick-walled basidiospores (8.5–19.5 × 7.5–11). Sequences of ITS and nLSU rRNA markers of the studied samples were generated, and the phylogenetic analyses were performed with maximum likelihood, maximum parsimony and bayesian inference methods on two datasets (ITS+nLSU and ITS). The analyses showed that the new species clustered into the genus Cyathus within the family Nidulariaceae based on the ITS+nLSU phylogenetic tree. The phylogenetic analyses based on molecular data from ITS sequences showed that C. tongxinianus is sister to C. annulatus, and groups with C. renweii.